ANALISIS KOMPREHENSIF PENINGKATAN KINERJA BISNIS MELALUI STRATEGI DESAIN BERBASIS PENGGUNA - Dewi Azizah Rosianti; Fhaya Frastystyandarum; Silvia Anggreani; Rusdi Hidayat N; Maharani Ikaningtyas (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Focusing on user-based design strategies to improve business performance is an innovative approach in today's digital era. Through comprehensive analysis, this research explores how design centered on user needs and preferences can improve operational efficiency, strengthen brands, and increase customer satisfaction. The method used includes narrative literature study using a qualitative approach through previous research. The research results show that user-based design strategies have great potential to improve business performance, with a clear impact on increasing customer retention, increasing operational efficiency and increasing customer satisfaction. This article provides practical advice for companies looking to implement user-based design strategies in their operations and highlights the importance of this approach in facing competitive challenges in the digital era.